THE ROLE OF “KERAPATAN ADAT NAGARI (KAN)” IN SOLVING THE DISPUTE OF COMMUNAL LAND - Faisal Bukhari (STIH Putri Maharaja, 2021)
According to miankabaunese’s traditional law, when a dispute or disagreement occurs in a community, it is resolved by consensus among members of the clan or clan leaders which ends in the fellowship of local custom assosiation called with “Kerapatan Adat Nagari (KAN)”. The problem formulation of this research is; what is the role of Kerapatan Adat Nagari (KAN) in resolving communal land (tanah Ulayat) disputes in one of local villager called Kenagarian Bukik Sikumpa, Lima Puluh Kota Regency? and how the efforts of Kerapatan Adat Nagari (KAN) to overcome obstacles in resolving communal land disputes in Kenagarian Bukik Sikumpa, Lima Puluh Kota Regency. The method of the research is an empirical juridical approach. The conclusion of research is that the role of Kerapatan Adat Nagari (KAN) of Bukik Sikumpa of Lima Puluh Kota district is as the mediator any disputes where the provisions of Perda No. 7 of 2018 as the legal basis. This provision declares that every local villagers have to prioritie in conducting local wisdom deliberation as solving problem among the family, community, and tribal levels. Kerapatan Adat Nagari (KAN) acts as an intermediary in resolving disputes if these three domains of local deliberation have been taken by the disputing families. Due to local religious philosophy